2022
DOI: 10.3390/ma15155331
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced N-Type Bismuth-Telluride-Based Thermoelectric Fibers via Thermal Drawing and Bridgman Annealing

Abstract: N-type bismuth telluride (Bi2Te3) based thermoelectric (TE) fibers were fabricated by thermal drawing and Bridgman annealing, and the influence of Bridgman annealing on the TE properties of n-type Bi2Te3-based TE fibers was studied. The Bridgman annealing enhanced the electrical conductivity and Seebeck coefficient because of increasing crystalline orientation and decreasing detrimental elemental enrichment. The TE performance of n-type Bi2Te3-based TE fibers was improved significantly by enhancing the power f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To date, it has been found that the n-type Bi 2 Te 3 fibers (thermally drawn with glass cladding by a powder-in-tube method) could exhibit a restricted ZT < 0.5 owing to the low relative density and more texturing-related sensitivity of the carriers’ mobility than their p-type fibers ( ZT ~1.4) [ 9 ]. In the thermoelectric fibers fabricated by thermal drawing from our previous works [ 14 , 15 , 16 , 17 ], the c -plane crystalline orientation enhances the carrier mobility and electrical conductivity in Bi 2 Te 3 core fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it has been found that the n-type Bi 2 Te 3 fibers (thermally drawn with glass cladding by a powder-in-tube method) could exhibit a restricted ZT < 0.5 owing to the low relative density and more texturing-related sensitivity of the carriers’ mobility than their p-type fibers ( ZT ~1.4) [ 9 ]. In the thermoelectric fibers fabricated by thermal drawing from our previous works [ 14 , 15 , 16 , 17 ], the c -plane crystalline orientation enhances the carrier mobility and electrical conductivity in Bi 2 Te 3 core fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, high-performance n-type Bi 2 Te 3 fibers were fabricated by a rod-in-tube thermal drawing method, and subsequent annealing processes (whole annealing and Bridgman annealing) were used to enhance the crystallization of two kinds of opposite crystalline orientations [ 17 ]. Crystalline orientations along (110) and (001) in the fiber cores were increased by whole annealing and Bridgman annealing, respectively, and the elemental enrichment was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Although TE materials are promising and have lots of advantages, predominant inorganic TE materials (such as Sb 2 Te 3 , Bi 2 Te 3 , etc.) are extremely limited in their application for wearable, portable, and implantable electronic devices and flexible robots due to the scarcity, toxicity, expensiveness, and difficulty in processing [ 8 , 9 , 10 , 11 ]. Fortunately, composites which consist of conductive polymers and fillers with different architectures, such as inorganic semiconductors or carbon nanoparticles, can balance properties with needs.…”
Section: Introductionmentioning
confidence: 99%